Evidence-Based Practices to Reduce Falls and Fall-Related Injuries Among Older Adults - Marcia G. Ory (Frontiers Research Topics, 2018)
Falls and fall-related injuries among older adults have emerged as serious global health concerns, which place a burden on individuals, their families, and greater society. As fall incidence rates increase alongside our globally aging population, fall-related mortality, hospitalizations, and costs are reaching never seen before heights. Because falls occur in clinical and community settings, additional efforts are needed to understand the intrinsic and extrinsic factors that cause falls among older adults; effective strategies to reduce fall-related risk; and the role of various professionals in interventions and efforts to prevent falls (e.g., nurses, physicians, physical therapists, occupational therapists, health educators, social workers, economists, policy makers). As such, this Research Topic sought articles that described interventions at the clinical, community, and/or policy level to prevent falls and related risk factors. Preference was given to articles related to multi-factorial, evidence-based interventions in clinical (e.g., hospitals, long-term care facilities, skilled nursing facilities, residential facilities) and community (e.g., senior centers, recreation facilities, faith-based organizations) settings. However, articles related to public health indicators and social determinants related to falls were also included based on their direct implications for evidence-based interventions and best practices.